TheEffect of Students Choukai Shochukyuu Capability PBJ UNNES on Value OF Test Choukai Nouryokushiken N4 - Nugraha, Adi Prabowo (Chi'e: Journal of Japanese Learning and Teaching, 2017)
The Capability to listen is an important ability in learning a foreign language. Choukai subjects is a subject which is given to improve listening skills Japanese. One effort to equip students Prodi Japanese Language Education in doing tests Choukai Nouryokushiken N4 is teaching Choukai Nouryokushiken types of test that exist in the textbook Nouryokushiken N4 no renshuu to students during the course Choukai Shochukyuu. However, the efforts made by teachers have not been implemented to the fullest because based on observations there are students who score Choukai Shochyukyuu good but a value Choukai Nouryokushiken unfavorable plus more, with an average value Choukai Nouryokushiken N4 of the lowest compared with bunpō, Moji Goi and dokkai. Therefore, this study aimed to determine whether there is influence Shouchukyuu Choukai ability of students to the value of the test Nouryokushiken Choukai N4 and to describe the presence or absence of causal factors that influence the ability of students to value Choukai Shochukyuu Choukai on tests Nouryokushiken N4. The approach used in this research is quantitative descriptive. The population in this study is the student of 2013 and 2014 Japanese Education Program UNNES follow Nouryokushiken N4 in 2014 and 2015. Data collection techniques in this study using documentation and questionnaires. Data analysis techniques in this study using the product moment, linear regression, coefficient of determination and descriptive percentage.Based on research result shows there is a relationship with a student's ability Choukai Shochukyuu Choukai Nouryokushiken value N4 class 2013 by 0,781, Class of 2014 of 0.77 and a combination of forces in 2013 and 2014 amounted to 0.752, while the influence of students' ability Choukai Shochukyuu Choukai grades on tests Nouryokushiken N4 force 2013 by 61% workforce in 2014 by 60% and the combination of forces in 2013 and 2014 by 56%. Based on the research questionnaire influential factors causing Shochukyuu Choukai ability to score on the test Nouryokushiken choukai N4 is very high at 98.76% is the influential factor in the constraints motivation. In orther side, Choukai ability Shochukyuu against Choukai on test results Nouryokushiken N4 which constraints are not the chance to repeat utterances native speaker, difficulties in interpreting speech, lack of adequate vocabulary and obstacles in recognizing the abbreviated sentence of native speaker pronunciation.